Synchronous diagnosis of anaplastic large cell lymphoma and multiple myeloma in a patient: A case report. Issue 44 (30th October 2020) - Shi, Xiaofeng; Wu, Jiannong; Jiang, Qian; Zhang, Shuo; Chen, Wanru; Yu, Xianqiu; Liu, Yichen; Chen, Min; Peng, Jie; Li, Tiantian; Zhu, Yan; Xi, Xiaodong
Abstract: Rationale: Synchronous development of both anaplastic large cell lymphoma (ALCL) and multiple myeloma (MM) in a patient is rare. To our knowledge, until now only one case has been reported. Treatment needs to cover both and is a challenge. Here we reported another case and discussed the diagnosis and treatment. Patient concerns: This is a 63-year old woman who presented with a mass in upper abdominal skin. Positron emission tomography/computed tomography (PET/CT) showed the high metabolism in left abdominal skin and left axillary lymph nodes. Histopathologic and immunohistochemical evaluation identified the cutaneous mass as an ALK-negative ALCL. Bone marrow smear showed increased plasma cells which expressed CD38, CD138, and cLambda concomitantly. The increased monoclonal immunoglobulin IgD λ was detected by immunofixation electrophoresis. Diagnoses: Diagnosis of both ALCL and MM was confirmed. Interventions: The patient successively received 6 cycles of B-CHOD regimen, one cycle of ID regimen, 2 cycles of DHAX regimen, one cycle of L-DA-EPOCH and autologous stem cell transplantation (ASCT). Then lenalidomide was performed as a maintenance therapy. Outcomes: Both ALCL and MM achieved complete remission. Lessons: We reported a very rare case with synchronous development of ALCL and MM, in whom a good therapeutic response to chemotherapies followed by ASCT has been observed.